Respons Pemberian Kompos Tandan Kosong Kelapa Sawit dan Zeolit Terhadap Pertumbuhan Bibit Kelapa Sawit di Pre Nursery - Gia Asra; Toga Simanungkalit; Nini Rahmawati (Universitas Sumatera Utara, 2015)
This research aims for knowing the response a giving of oil palm seeds in the results of giving empty fruit bunches of oil palm compost and zeolite in pre nursery. The researched was carried outat Faculty of Agricultural screen house, USU (± 25 mdpl) in March – July 2014 using a randomizedblock design with two factors. The first factors was dose empty fruit brunches of oil palm compostwith four levels that were including 0 g/polybag; 15 g/polybag; 30 g/polybag; 45 g/polybag; andthe second factor was dose of zeolite with four levels that were including 0 g/polybag; 5 g/polybag;10 g/polybag; 15 g/polybag. The results of research shows that the application of empty fruitbrunches of oil palm compost had a real impact on the stem diameter and total leaf area. As for thediameter of stem best level was obtained at treatment EFBOP compost 45 g/polybag and total leafbest level was obtained at treatment EFBOP compost 30 g/polybag. Giving the zeolite wasevidently influencial toward the stem diameter, total leaf area, crowns wetness weight, root drynessweight, and crowns dryness weight. Zeolite best level was obtained at treatment zeolite 5g/polybag. The interaction between empty fruit brunches of oil palm compost and zeolite fertilizerwas evidently influencial towards the total leaf area and crowns dryness weight in pre nursery. Besttreatment combination level was found of which was 30 g/polybag of empty fruit brunches of oilpalm compost and5 g/polybag of zeolite. Key words: EFBOP compost, zeolite, and oil palm